ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SEKOLAH MENENGAH PERTAMA (SMP) KELAS IX - ANANDA, CHEVIN; U.S, SUPARDI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
The purpose of this research is to determine the level of students 'problem solving abilities, and students' abilities at each stage of problem solving. This study used qualitative research methods. The sample in this study were students of class IX, to determine the research subject using a purposive sample, 3 subjects were selected to represent the 3 categories of students' problem solving abilities to provide information about problem solving abilities for each criterion. The methods used to collect data are test, interview and documentation methods. The steps in data analysis are reduction, presentation, and drawing conclusions. Based on the research, it can be concluded that: out of 10 students, 2 students (20%) had the problem solving ability in the